2017
DOI: 10.1186/s13756-017-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

The function of the thyroid gland in patients with multi-drug resistant tuberculosis

Abstract: BackgroundMultidrug-resistant tuberculosis (MDRTB) remains a health problem for many countries in the world. The share of MDRTB is 10–30% among newly diagnosed cases and 20–70% among relapses and treatment failure. The aim of the study is to define the side effects of second line drugs used in the treatment of MDRTB on thyroid function.MethodsIn 30 patients with multidrug resistant tuberculosis, echostructure of thyroid was studied by ultrasound imaging method. Indices of thyroid function: plasma levels of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…At the same time, in the comparison group, the average level of free thyroxine significantly decreased, and the average level of thyroid-stimulating hormone significantly increased by the end of the intensive therapy phase. The results obtained indicate a negative effect of second-line anti-tuberculosis drugs (ethionamide, prothionamide and PAS and others) on thyroid function, which was observed in other studies [13]. This fact necessitates timely screening of thyroid function during the treatment of drug-resistant tuberculosis.…”
Section: Resultssupporting
confidence: 53%
“…At the same time, in the comparison group, the average level of free thyroxine significantly decreased, and the average level of thyroid-stimulating hormone significantly increased by the end of the intensive therapy phase. The results obtained indicate a negative effect of second-line anti-tuberculosis drugs (ethionamide, prothionamide and PAS and others) on thyroid function, which was observed in other studies [13]. This fact necessitates timely screening of thyroid function during the treatment of drug-resistant tuberculosis.…”
Section: Resultssupporting
confidence: 53%
“…Studies included in this review were reported from 19 countries which cover three continents (Africa, Asia and Europe) [Table 1]. Seventeen studies were reported from Asian [32,3440,4244,46,48,53,54,60,61], eight from African [41,45,47,49,50,55,57,58] and five from European [33,48,52,56,59] countries. We categorized Russia, Turkey and Ukraine under European countries category.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty four studies were based on health facility (hospital, TB clinic, research center and MDR-TB treatment center), while six were community based [Table 1]. In terms of study design, 15 were retrospective cohort study, 13 prospective cohort study, one ambispective cohort study [61] and one study [48] has not reported the study design [Table 1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation